Detection of 16 Gamma-Ray Pulsars Through Blind Frequency Searches Using the Fermi LAT - Abdo, A.; Ackermann, M.; Ajello, M.; Anderson, B.; Atwood, W.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M.; Bastieri, D.; Baughman, B.; et al. (The American Association for the Advancement of Science, 2009)
Pulsars are rapidly rotating, highly magnetized neutron stars emitting radiation across the electromagnetic spectrum. Although there are more than 1800 known radio pulsars, until recently only seven were observed to pulse in gamma rays, and these were all discovered at other wavelengths. The Fermi Large Area Telescope (LAT) makes it possible to pinpoint neutron stars through their gamma-ray pulsations. We report the detection of 16 gamma-ray pulsars in blind frequency searches using the LAT. Most of these pulsars are coincident with previously unidentified gamma-ray sources, and many are associated with supernova remnants. Direct detection of gamma-ray pulsars enables studies of emission mechanisms, population statistics, and the energetics of pulsar wind nebulae and supernova remnants.